Carbon ion radiotherapy decreases the impact of tumor heterogeneity on radiation response in experimental prostate tumors - Glowa, Christin; Karger, Christian; Brons, Stephan; Huber, Peter E.; Debus, Jürgen; Peschke, Peter (Cancer letters, 2016)
Objective To quantitatively study the impact of intrinsic tumor characteristics and microenvironmental factors on local tumor control after irradiation with carbon (12C-) ions and photons in an experimental prostate tumor model. Material and Methods Three sublines of a syngeneic rat prostate tumor (R3327) differing in grading (highly (-H) moderately (-HI) or anaplastic (-AT1)) were irradiated with increasing single doses of either 12C-ions or 6 MV photons in Copenhagen rats. Primary endpoint was local tumor control within 300 days. The relative biological effectiveness (RBE) of 12C-ions was calculated from the dose at 50% tumor control probability (TCD50) of photons and 12C-ions and was correlated with histological, physiological and genetic tumor parameters. Results Experimental findings demonstrated that (i) TCD50-values between the three tumor sublines differed less for 12C-ions (23.6-32.9 Gy) than for photons (38.2-75.7 Gy), (ii) the slope of the dose-response curve for each tumor line was steeper for 12C-ions than for photons, and (iii) the RBE increased with tumor grading from 1.62 ± 0.11 (H) to 2.08 ± 0.13 (HI) to 2.30 ± 0.08 (AT1). Conclusion The response to 12C-ions is less dependent on resistance factors as well as on heterogeneity between and within tumor sublines as compared to photons. A clear correlation between decreasing differentiation status and increasing RBE was found. 12C-ions may therefore be a therapeutic option especially in patients with undifferentiated prostate tumors, expressing high resistance against photons.